Structure-activity relationships of polybiguanides with activity against human immunodeficiency virus type 1 - Passic, Shendra R. (2010)
Previous investigations showing that polydisperse biguanide (PDBG) molecules have activity against human immunodeficiency virus type 1 (HIV-1) also suggested a relationship between PDBG biologic activity and the lengths of hydrocarbon linkers surrounding the positively charged biguanide unit. To better define structure-activity relationships, PDBG molecules with select linker lengths were evaluated for cytotoxicity, anti-HIV-1 activity, and in vivo toxicity. Results of the in vitro experiments demonstrated that increases in linker length (and, therefore, increases in compound lipophilicity) were generally associated with increases in cytotoxicity and antiviral activity against HIV-1. However, a relationship between linker length asymmetry and in vitro therapeutic index (TI) suggested structural specificity in the mechanism of action against HIV-1. Polyethylene hexamethylene biguanide (PEHMB; biguanide units spaced between alternating ethylene and hexamethylene linkers) was found to have the highest in vitro TI (CC(50)/IC(50)) among the compounds examined. Recent improvements in PEHMB synthesis and purification have yielded preparations of PEHMB with in vitro TI values of 266 and 7000 against HIV-1 strains BaL and IIIB, respectively. The minimal toxicity of PEHMB relative to polyhexamethylene biguanide (PHMB; biguanide units alternating with hexamethylene linkers) in a murine model of cervicovaginal microbicide toxicity was consistent with considerable differences in cytotoxicity between PEHMB and PHMB observed during in vitro experiments. These structure-activity investigations increase our understanding of PDBG molecules as agents with activity against HIV-1 and provide the foundation for further preclinical studies of PEHMB and other biguanide-based compounds as antiviral and microbicidal agents.